2000
DOI: 10.1016/s1388-2457(00)00360-6
|View full text |Cite
|
Sign up to set email alerts
|

Spectro-temporal analysis of complex tones: two cortical processes dependent on retention of sounds in the long auditory store

Abstract: Objectives: To examine whether two cortical processes concerned with spectro-temporal analysis of complex tones, a`C-process' generating CN1 and CP2 potentials at cf. 100 and 180 ms after sudden change of pitch or timbre, and an`M-process' generating MN1 and MP2 potentials of similar latency at the sudden cessation of repeated changes, are dependent on accumulation of a sound image in the long auditory store.Methods: The durations of steady (440 Hz) and rapidly oscillating (440±494 Hz, 16 changes/s) pitch of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Due to interference from ERP activity around the offset of the pause interval in the unphrased condition (possibly caused by some auditory processing related to the pausefilling notes), an exact quantification of this effect is not possible. It might, however, be related to the refractoriness mechanism of the neural system (Budd et al, 1998;Jones et al, 2000). In the time range between 100 and 450 ms, the ERP did not only react to the phrase boundary, but it was also affected by the different musical styles and the cultural backgrounds of the subjects.…”
Section: Early Effects Of Phrasingmentioning
confidence: 93%
“…Due to interference from ERP activity around the offset of the pause interval in the unphrased condition (possibly caused by some auditory processing related to the pausefilling notes), an exact quantification of this effect is not possible. It might, however, be related to the refractoriness mechanism of the neural system (Budd et al, 1998;Jones et al, 2000). In the time range between 100 and 450 ms, the ERP did not only react to the phrase boundary, but it was also affected by the different musical styles and the cultural backgrounds of the subjects.…”
Section: Early Effects Of Phrasingmentioning
confidence: 93%
“…Our own studies of auditory evoked potentials (AEPs) to complex harmonic tones have shown that different events give rise to N1/P2 complexes with different scalp distributions (Jones et al, 1998(Jones et al, , 2000. The ''change-type'' N1/P2 complex (termed ''C-potentials'') peaking at 100-200 ms following an abrupt redistribution of spectral energy is maximal in the fronto-central region, and is believed to be concerned with a process of ''spectral profile analysis'' (Jones and Perez, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…7 The chief distinction between the long auditory store and verbal working memory is that in the former sounds are represented in a precategorical state, effectively as an acoustic image. It is arguable, however, that verbal working memory may depend to some degree on the "rehearsal" of material through precategorical levels of acoustic storage.From our previous studies of long latency AEPs to complex harmonic tones (synthesised musical instrument sounds) [8][9][10] we have distinguished at least two neuronal populations of the supratemporal cortex, responsive to different types of change in the spectrotemporal structure of the sound. A negative potential peaking at approximately 90 ms and a positivity at 160 ms are produced by sudden, infrequently occurring changes in the distribution of energy across the audible frequency spectrum.…”
mentioning
confidence: 99%
“…From our previous studies of long latency AEPs to complex harmonic tones (synthesised musical instrument sounds) [8][9][10] we have distinguished at least two neuronal populations of the supratemporal cortex, responsive to different types of change in the spectrotemporal structure of the sound. A negative potential peaking at approximately 90 ms and a positivity at 160 ms are produced by sudden, infrequently occurring changes in the distribution of energy across the audible frequency spectrum.…”
mentioning
confidence: 99%
See 1 more Smart Citation